Pemaknaan dan Simbolisasi Ikan dalam Khazanah Naskah Melayu: Analisis Semiotika Roland Barthes - Putra, Ragil; Buduroh, Mamlahatun (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2023)
Al-Attas in one of his sub-chapters mentions the use of the word 'Ikan Tunggal' (Unique Fish) in one of Hamza Fansuri's works entitled Sha’ir Jawl fasal fl bayan ‘Ilm al-Suluk wa’l-Tawhid. "Ikan Tunggal" or Unique Fish is a symbol of the Spirit, or can be interpreted as 'soul' or 'al-Ruh'. The problem discussed is whether the meaning of "ikan" brought by Hamza Fansuri affects the meaning of "ikan" in Malay texts or not. The corpus data used comes from the Malay Concordance Project by utilizing the direct search and chronological order features to bring up the word "ikan" in different texts and periods. This is qualitative research and the collected data would be analyzed with descriptive methods. All the collected data would be interpreted one by one according to the context in the text itself and with some addition to the secondary data, which is another research to support the arguments. The results of this paper conclude that the concept of "ikan" brought by Hamza Fansuri was not immediately accepted and followed by Malay authors and copyists because they still have their own variety. However, two works are excluded from interpreting "ikan" with such a concept, namely "ikan" as a sign in a dream and "ikan" as a catastrophic phenomenon from Allah SWT.Keyword: Hamzah Fansuri; Al-Attas; Ikan; Naskah Melayu; Semiotics; Roland Barthes.